Studi Kelayakan Destinasi Wisata Ramah Muslim untuk Meningkatkan Citra Wisata di Sumenep (Studi Kasus Pantai Lombang dan Pantai e-Kasoghi Kabupaten Sumenep) - Rozi, Fachrur; Camelia, Allyvia (Fakultas Syariah INSURI Ponorogo, 2022)
According to the Minister of tourism and creative economy, Sandiaga Uno, Muslim Friendly Tourism which is one of the advantages of tourism from various types that are developed. The concept of Muslim friendly tourism is Halal tourism that referred to an extension of service or an increase and expansion of services, it does not mean that it is a tourist place. This concept is a brilliant idea in ensuring the comfort of Muslim tourists in tourist places, because Indonesia is a Muslim-majority country. Indeed the concept of a feasibility study there are several items as a guide to measure the feasibility of a tourist destination in this case such as Attraction, Accessibility, Community Socio-Economic Environmental Conditions, Accommodation, Supporting Facilities and Infrastructure, Security, Relationships with Other Tourist Objects. This feasibility study was conducted to see the readiness of tourist destinations as pilot destinations in Sumenep district. This location was chosen because Lambang beach is a tourist destination managed by the government and has become an icon of marine tourism in Sumenep, while e-Kasoghi beach is a new destination managed by local (private) villages. In addition, the COVID-19 pandemic demands many things, especially tourist destinations that must follow the health protocols that have been instructed by the central government to ensure tourists are safe and comfortable while at tourist locations. CHSE certification is the application of health protocols based on Cleanliness, Health, Safety, and Environment Sustainability. This is a health regulation or protocol with the term CHSE.